Red cell volume response to exercise training: Association with aging - Montero, D.; Lundby, C. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Red blood cell volume (RBCV) is a main determinant of cardiorespiratory fitness in healthy individuals. However, it remains controversial to what extent exercise training (ExT) enhances RBCV. Therefore, we sought to systematically review and determine the effect of ExT on RBCV in healthy individuals across all ages. We conducted a systematic search of MEDLINE, Scopus, and Web of Science, since their inceptions until February 2016 for articles assessing the effect of ExT interventions (not including hypoxic training) on blood volumes in healthy individuals. A meta-analysis was performed to determine the mean difference (MD) in RBCV between post- and pre-ExT measurements. Thirty studies were included after systematic review, comprising a total of 299 healthy individuals (mean age = 19-71 years, 271 males). Exercise training programs primarily consisted in lower limb endurance training interventions (mean duration = 15.2 weeks). After data pooling, RBCV was not increased following ExT (MD = 49 mL, 95% CI = -11, 108; P = 0.11). In subgroup analyses, RBCV was increased after ExT in young and middle-aged individuals (mean age <60 year) (n = 106, MD = 81 mL, 95% CI = 0, 162; P < 0.05) but not in older study participants (mean age =60 year) (n = 110, MD = 13 mL, 95% CI = -76, 102; P = 0.77). Heterogeneity was not detected among studies in young and middle-aged (I2 = 0%) and older individuals (I2 = 0%). In conclusion, RBCV is moderately, yet consistently, enhanced by ExT in young and middle-aged but not in older healthy individuals. Therefore, RBCV adaptations to ExT appear to be age dependent.